USM TO PURSUE FURTHER COLLABORATIONS WITH CSCSE THROUGH EXCHANGE PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 22 November 2016 Universiti Sains Malaysia (USM) today received an official courtesy visit from the Chinese Service Center for Scholarly Exchange (CSCSE).